Effectiveness of models of degradation of functional parameters for predicting the parametric reliability of semiconductor devices - S. M. Borovikov; N. I. Tsyrelchuk; S. S. Dick; E. N. Shneiderov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
For semiconductor devices of high power, the authors experimentally obtained of models of functional degradation parameter in the form of the conditional density of its distribution under the assumption of three hypotheses about the distribution law at the points of operating time: normal, two-parameter exponential and Weibull-Gnedenko. Using the average prediction error, the authors compared the effectiveness of degradation models in determining of the parametric reliability of new samples of semiconductor devices of the same type.